2020
DOI: 10.1210/clinem/dgaa337
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitizers for Improving the Endocrine and Metabolic Profile in Overweight Women With PCOS

Abstract: Objective To evaluate the efficacy of insulin sensitizers on menstrual frequency, sex hormone, and metabolic parameters in overweight women with polycystic ovary syndrome (PCOS). Methods We searched multiple databases from inception to September 2019 for randomized controlled trials. Network meta-analysis was conducted using multivariate random effects method. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 52 publications
(52 reference statements)
2
45
0
Order By: Relevance
“…The TMA also demonstrated that Met + TZDs was superior to Met monotherapy at reducing FINS and TC level. Our previous NMA in overweight women with PCOS revealed that Met + TZDs was superior to Met in recovering menstrual function, whereas there were no evident differences in TT and FINS [ 44 ]. Different inclusion criteria might explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TMA also demonstrated that Met + TZDs was superior to Met monotherapy at reducing FINS and TC level. Our previous NMA in overweight women with PCOS revealed that Met + TZDs was superior to Met in recovering menstrual function, whereas there were no evident differences in TT and FINS [ 44 ]. Different inclusion criteria might explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report on the analysis of efficacy of Met and MI + DCI in women with PCOS; it revealed that among all of the agents investigated here MI + DCI appeared to be the best intervention for restoring regular menses and decreasing HOMA-IR, while the combination was also able to reduce TT better than Met. No side effects have been described in clinical studies examining the effect of inositol [ 26 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinediones (TZDs) are a well-known family of drugs used to improve levels of lipids and glucose, mainly in T2DM (but they are also applied to nonalcoholic steatohepatitis, psoriasis, autism and other conditions) [ 136 ]. For PCOS treatment, TDZs were successfully used in combination with metformin [ 137 ] and other natural compounds (such as inositol and α-lipoic acid) [ 138 ], improving metabolic and endocrine parameters. However, TDZs had worsening weight gain that is considered a main negative side effect [ 139 ].…”
Section: Pcos Treatments: Classical and Modern Mitochondria–oriented Approachesmentioning
confidence: 99%
“…This is the rst report on the analysis of e cacy of Met and MI + DCI in women with PCOS; it revealed that among all of the agents investigated here MI + DCI appeared to be the best intervention for restoring regular menses and decreasing HOMA-IR, while the combination was also able to reduce TT better than Met. No side effects have been described in clinical studies examining the effect of inositol [26,44]. Berberine (BBR), a natural isoquinoline alkaloid, has been studied in various randomized clinical trials in patients with PCOS and has been shown to be safe and promising for decreasing insulin resistance, lowering blood lipids, and restoring ovulation [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%